Insights Into Bloodstain Degradation and Time Since Deposition Estimation Using Electrochemistry - Tiessen, Mitchell; Fruehwald, Holly M.; Easton, E. Bradley; Stotesbury, Theresa (Frontiers in Analytical Science, 2022)
Blood is an important type of forensic evidence because it can be used for source identification, toxicological analyses, and bloodstain pattern interpretation. Determining the time that bloodshed occurred, often described as the bloodstain’s time since deposition (TSD), has important implications for crime scene investigation. In this work, we focus on using electrochemical methods to monitor the gradual oxidative changes and electron-transfer reactions of hemoglobin (Hb) occurring in degrading bloodstains using differential pulse and hydrodynamic voltammetry. Bloodstains were monitored across a two-week time series in 5 different temperature conditions. Linear mixed models generated from the differential pulse voltammograms (DPV) suggested that 7 of 27 variables related to the redox reactions associated with the blood film were significantly correlated with time (p < 0.033). Of these correlated variables, all were related to the reduction of bound oxygen to hemoglobin or the oxidation of hemoglobin degradation products within the film. Hydrodynamic voltammetry demonstrated that hemoglobin retains its catalytic activity for oxygen reduction when aged on an electrode surface with a shift to greater peroxide formation the longer it is aged. The time series models are improved when the biological replicate is considered as a random effect, and as well as when peak area ratios are included in the model. Interestingly, using linear mixed models we observed a significant change in redox response at the 96-hour time point (p < 0.043) regardless of temperature condition. Overall, we demonstrate preliminary support for DPV as a technique for TSD estimation of bloodstains.